2001
DOI: 10.1097/00000658-200108000-00004
|View full text |Cite
|
Sign up to set email alerts
|

2,500 Living Donor Kidney Transplants: A Single-Center Experience

Abstract: ObjectiveTo review a single center's experience and outcome with living donor transplants. Summary Background DataOutcome after living donor transplants is better than after cadaver donor transplants. Since the inception of the authors' program, they have performed 2,540 living donor transplants. For the most recent cohort of recipients, improvements in patient care and immunosuppressive protocols have improved outcome. In this review, the authors analyzed outcome in relation to protocol. MethodsThe authors st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
146
1
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(168 citation statements)
references
References 44 publications
14
146
1
7
Order By: Relevance
“…Other studies have also found a negative effect of smoking (43)(44)(45). Of the 279 patients who were investigated in an Austrian study (45), smokers had higher serum creatinine values (2.3 Ϯ 2.7 versus 1.8 Ϯ 1.4 mg/dl; P ϭ 0.21) and tended to develop transplant failure (33.3 versus 21.2%; P ϭ 0.25).…”
Section: Patients With a Renal Transplantmentioning
confidence: 91%
“…Other studies have also found a negative effect of smoking (43)(44)(45). Of the 279 patients who were investigated in an Austrian study (45), smokers had higher serum creatinine values (2.3 Ϯ 2.7 versus 1.8 Ϯ 1.4 mg/dl; P ϭ 0.21) and tended to develop transplant failure (33.3 versus 21.2%; P ϭ 0.25).…”
Section: Patients With a Renal Transplantmentioning
confidence: 91%
“…Medical or surgical complications can occur following renal transplant in up to 10% of patients [3,4]. Surgical complications usually encountered include ureteral problems (obstruction, urinoma, or lymphocele) or vascular problems (stenosis or thrombosis of renal artery, arterio venous fistula, thrombosis of renal vein or iliac vein, bleeding, perigraft hematoma or pseudo aneurysm).…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, the quality of donor organs determines transplant outcome. 12 It is well known that living donor organs function better than those from deceased donors. Accordingly, the biomarkers for kidney transplantation can be divided into two types: biomarkers for living donors, and biomarkers for deceased donors.…”
Section: Different Types Of Biomarkers For Renal Allograft Monitoringmentioning
confidence: 99%